KAJIAN KONSUMSI ENERGI BEBERAPA JENIS PRODUK INDUSTRI KAYU - Tjutju Nurhayati (Jurnal Penelitian Hasil Hutan, 1992)
The purpose of this study is to identify the energy consumption fram PLN (state electric company) electricity, diesel fuel and wood waste per m3 production of several products of wood indutries. The products included in the study are plywood, jointing board, matches and chopstick wood working, housing component, particleboard, picture frame and sawntimber.The study revealed that energy consumption from PLN electricity per m3 productions for plywood was 149. 51 kwh, jointing board was 152.29 kw, sawntimber ranged from 34.25 to 55.87 kwh and wood working was 178.11 kwh. The consumptions of diesel fuel for plywood was 50. 97 liters, and sawntimber was 14.23 liters. The biomass energy consumption per m3 productions for picture frame was 0.08 m3 which gave the lowest figure while the highest was for jointing board, namely 0. 604 m3. the share of biomass energy per m3 productions was 82% of the total energy consumption.